Annealing effects on self-assembled TiO2 nanotubes and their behavior as photoelectrodes in dye-sensitized solar cells - Vaenas, N.; Bidikoudi, M.; Stergiopoulos, T.; V. Likodimos; A. G. Kontos; P. Falaras (Chemical Engineering Journal, 2013)
Self-assembled highly ordered TiO2 nanotube arrays were grown on Ti foils in NH4F ethylene glycol electrolyte under mild anodic oxidation conditions. The effect of annealing post-treatment on their structural properties was systematically investigated with respect to their electrical characteristics and photoelectrochemical performance in back-side illuminated dye-sensitized solar cells (DSCs). A variety of parameters was controlled and optimized including the annealing temperature, the heating rate and duration of the thermal treatment. The obtained results confirmed a correlation between the crystalline/structural properties of the TiO2 nanotubes and their electrical characteristics, thus revealing the close interplay of crystal size, grain boundaries and crystallite interconnectivity with the electron dynamics (transport/ recombination) governing the DSC operation and efficiency. The high importance of a barrier layer at the interface between the nanotubes and the Ti foil was also highlighted. © 2013 Elsevier B.V.
cited By 14